Analysis of The Cooling Spray System for Hot Pool Water With An Electricity Source from Solar Cells - bambang irawan; Syamsul Hadi; Samsul Hadi; kris witono (Journal of Evrímata: Engineering and Physics, 2023)
This study discusses the cooling of water with a system of spraying it into the free air. The energy source to drive the pump uses energy from sunlight. This research is to solve a problem in an area where it is difficult to get water so that the water for the cooling process must be cooled so that it can be used for the next process. The second problem is that the electrical energy is very minimal, so you have to use other energy that can be used for the cooling process. The process of cooling the water spray system into the air was chosen to solve this problem. The tools used in this study were a 600 Wp solar cell, a 300 W water pump and a spray pipe. The research was conducted during the dry season in August. The research results show that the temperature of the water in the pool is not homogeneous the deeper the water in the pool the lower the temperature. The higher the pool water temperature, the longer the cooling time will be. The greater the pump discharge, the faster it will take to cool the pool water. Solar energy is able to supply energy to drive pumps with pool water temperatures up to 45 C. This cooling system can be used at night because it is equipped with batteries. The results of this research can be used and developed to create a larger system. This cooling system does not cause any impact on the environment because the energy source is from sunlight which is environmentally friendly.